Comparison of minimally invasive decompression and combined minimally invasive decompression and fusion in patients with degenerative spondylolisthesis with instability. (November 2018) - Hayashi, Kazunori; Toyoda, Hiromitsu; Terai, Hidetomi; Hoshino, Masatoshi; Suzuki, Akinobu; Takahashi, Shinji; Tamai, Koji; Ohyama, Shoichiro; Hori, Yusuke; Yabu, Akito; Nakamura, Hiroaki
Highlights: We investigated surgical treatments for unstable degenerative spondylolisthesis. Two forms of surgical treatment were compared: (1) Posterior lumbar interbody fusion with cortical bone trajectory (CBT-PLIF); (2) Microendoscopic laminotomy (MEL). Clinical outcomes were similar, but MEL was less invasive. MEL can be an alternative surgical method, as well as CBT-PLIF. Abstract: Posterior lumbar interbody fusion with cortical bone trajectory (CBT-PLIF) is a form of minimally invasive decompression and fusion, whereas microendoscopic laminotomy (MEL) is a form of minimally invasive decompression surgery. No study has compared the clinical outcomes of the two methods for patients who have degenerative spondylolisthesis (DS) with instability. In this study, CBT-PLIF and MEL were both offered to 64 patients who met the inclusion criteria. Each patient then selected his or her preferred treatment. Twenty patients received CBT-PLIF. They were matched to 30 of the 44 patients receiving MEL based on age, sex, disease duration, and surgical levels. The 20 patients with CBT-PLIF formed the CBT group and the 30 matched patients with MEL formed the MEL group. At 2 years of follow-up, Japanese Orthopaedic Association scores improved to 72.6% and 70.5% in the CBT and MEL groups, respectively. The difference in scores was not statistically significant. Further, improvements in visual analogue scale scores for back and leg symptom did not differ significantly between the two groups. Regarding complications, 1 CBT-group patient (5%) had adjacent-segment degeneration and 7 MEL-group patients (23%) had same-segment degeneration. Three CBT-group patients (15%) and 5 MEL-group patients (16%) required reoperation within the follow-up period. In summary, among patients who had DS with instability, MEL and CBT-PLIF offered comparable clinical outcomes at 2 years of follow-up. Although the rate of segmental degeneration was relatively high in the MEL group, both groups had similar reoperation rates.